Lost to the state: family discontinuity, social orphanhood and residential care in the Russian Far East - Rockhill, Elena Khlinovskaya (Berghahn Books, 2010)
Childhood held a special place in Soviet society: seen as the key to a better future, children were imagined as the only privileged class. Therefore, the rapid emergence in post-Soviet Russia of the vast numbers of vulnerable 'social orphans', or children who have living relatives but grow up in residential care institutions, caught the public by surprise, leading to discussions of the role and place of childhood in the new society. Based on an in-depth study the author explores dissonance between new post-Soviet forms of family and economy, and lingering Soviet attitudes, revealing social orphans as an embodiment of a long-standing power struggle between the state and the family. The author uncovers parallels between (post-) Soviet and Western practices in child welfare and attitudes towards 'bad' mothers, and proposes a new way of interpreting kinship where the state is an integral member.